Silage Crops for Dairy and Beef Cattle II: Sorghum and Other Forage Crops - Marcelo Wallau; Joao Vendramini; Adegbola Adesogan; Diwakar Vyas; Kevin Korus (EDIS)
This publication is a second article on silage crops for dairy and beef cattle that explores crop choices and agronomic aspects of silage production in Florida, from planting until preparing to harvest for sorghum, sorghum x sudan, pearl millet, and cool-season small grain silages. Written by Marcelo Wallau, Joao Vendramini, Adegbola Adesogan, Diwakar Vyas, and Kevin Korus, and published by the UF/IFAS Agronomy Department, February 2022.